Multimodal Discourse Analysis of Studio Ghibli Movie Posters: (Study of Studio Ghibli Movie Posters 1984-2023) - Yudhanto, Sigied Himawan (Journal of Visual Art and Design, 2024)
Ghibli Studio's animated film posters are visually beautiful, with a unique, alluring art style that reflects the story's essence. The images of the posters are eye-catching and portray nuances and emotions that have become very iconic in the world of animation. This research method used Fairclough's critical discourse analysis model and Kress and van Leeuwen's visual grammar in the context of visual semiotics to find the meaning behind the posters of Studio Ghibli animated films. The research method used was multimodal discourse analysis combined with a descriptive qualitative approach and quantitative narratives. The purpose of this study was to identify the use of a specific visual language in Studio Ghibli film posters, employing the visual grammar framework of three metafunctions in semiotics as an explorative tool to find out how these elements can strengthen visual messages and themes within the multimodal discourse analysis framework. The contribution of this research is the examination of the visual and textual aspects of film poster media to increase public awareness of the importance of discourse analysis in interdisciplinary science, namely the combination of visual communication design and systemic functional linguistics (SFL).